Human and porcine aortic valve endothelial and interstitial cell isolation and characterization - Nehl, D.; Goody, P. R.; Maus, K.; Pfeifer, A.; Aikawa, E.; Bakthiary, F.; Zimmer, S.; Nickenig, G.; Jansen, F.; Hosen, M. R. (Frontiers in Cardiovascular Medicine, 2023)
Background Calcific aortic valve stenosis (AVS) is defined by pathological changes in the aortic valve (AV) and their predominant cell types: valvular interstitial (VICs) and endothelial cells (VECs). Understanding the cellular and molecular mechanisms of this disease is a prerequisite to identify potential pharmacological treatment strategies. In this study, we present a unique aortic valve cell isolation technique to acquire specific human and porcine cell populations and compared VICs and VECs of these species with each other for the first time. Methods AV cells were isolated from tissue obtained from human patients undergoing surgical aortic valve replacement (SAVR) or from porcine hearts. Functional analysis and in vitro experiments revealed that endothelial-to-mesenchymal transition (EndMT) can be induced in hVECs, leading to a significant increase in mesenchymal markers. In vitro calcification experiments of VICs demonstrated pronounced expression of calcification markers and visible calcific deposits in Alizarin Red staining in both species after incubation with pro-calcific media. Results Cells isolated from patient-derived AVs showed mesenchymal and endothelial-specific gene signatures (VIC and VEC, respectively). For instance, von Willebrand factor (vWF) and platelet endothelial adhesion molecule-1 (PECAM1) were upregulated in VECs, while the myofibroblastic markers alpha-smooth muscle actin (α-SMA) and vimentin (VIM) were downregulated in VECs compared to VICs. Analysis of cell function by migration revealed that VECs are more migratory than VICs. Induction of EndMT in vitro in VECs displayed increased expression of EndMT markers and decreased expression of endothelial markers, confirming their mesenchymal transdifferentiation ability. In vitro calcification of VICs revealed upregulation of alkaline phosphatase (ALPL), a hallmark of calcification. In addition, other calcification-related genes such as osteocalcin (BGLAP) and runt-related factor 2 (RUNX2) were upregulated. Alizarin red staining of calcified cells provided a further layer of confirmation that the isolated cells were VICs with osteoblastic differentiation capacity. Conclusion This study aims to take a first step towards standardizing a reproducible isolation technique for specific human and porcine VEC and VIC populations. A comparison of human and porcine aortic valve cells demonstrated that porcine cells may serve as an alternative cellular model system in settings where human tissue is difficult to obtain.